Defending The State in The Digital Domain: Between Cyber Threats and National Awareness - Rika Githamala Ginting; Gatot Teguh Arifyanto; Fauzan Ghafur (Academic Solution Publisher, 2025)
Cyber threats are a big challenge for Indonesia along with the development of digital technology and dependence on cyberspace. This article aims to analyze the relationship between cyber threats and digital national defense and the role of national awareness in strengthening state resilience. This qualitative research with a literature analysis shows that Indonesia faces major challenges in digital resilience, such as low digital literacy, inadequate infrastructure, and limited experts in the field of cybersecurity. In conclusion, collaboration between the government, the private sector, and the community as well as increased digital literacy is needed to strengthen Indonesia's cyber resilience.